Sanksi Pidana Perampokan dalam Kitab Undang-Undang Hukum Pidana dan Hukum Pidana Islam - Ishaq Ishaq (AHKAM : Jurnal Ilmu Syariah, 2015)
This study aimed to find robbery criminal justice in KUHP and Jinayah perspectives. Robbery criminal justice is mentioned on Article 365 of Criminal Code, consisting of: prison nine, twelve, fifteen, and the death penalty, or life imprisonment or imprisonment for over twenty years. Meanwhile, in Islamic law, based on al-Qur’an, al-Ma’idah (5) verse 33 sated that the justice are sentenced to death by violently and authoritative, cross sentenced to death or executed after some time he hung, cut off his hands and legs intersect, and banished from the earth.DOI: 10.15408/ajis.v15i2.2858